Cortical superficial siderosis, hematoma volume, and outcomes after intracerebral hemorrhage: a mediation analysis - Jin, Yu-jia; Li, Jia-wen; Wu, Jian; Huang, Yu-hui; Yang, Kai-cheng; An, Hong-na; Yuan, Chang-zheng; Gao, Feng; Tong, Lu-sha (Frontiers in Neurology, 2023)
Background: Previous studies have shown that cortical superficial siderosis (cSS) can increase hematoma volume and predict poor outcomes following primary intracerebral hemorrhage (ICH). Objective: We aimed to extrapolate whether a large hematoma volume was the essential factor contributing to worse outcomes because of cSS. Methods: Patients with spontaneous ICH underwent a CT scan within 48 h after ictus. cSS was evaluated using magnetic resonance imaging (MRI) within seven days. The 90-day outcome was assessed using the modified Rankin Scale (mRS). In addition, we investigated the correlation between cSS and hematoma volume and 90-day outcomes using multivariate regression and mediation analyses. Results: Among the 673 patients with ICH, 131 (19.5%) had cSS. cSS was associated with larger hematoma volume (β = 4.449, 95% CI 1.890–7.009, p < 0.001) independent of hematoma location and was also related to worse 90-day mRS (β = 0.333, 95% CI 0.008-0.659, p = 0.045) in multivariable regression. In addition, mediation analyses revealed that hematoma volume was an essential factor mediating the effect of cSS on unfavorable 90-day outcomes (proportion mediated:66.04%, p = 0.01). Conclusion: Large hematoma volume was the major charge of directing cSS to worse outcomes after ICH. cSS was related to a larger hematoma in both lobar and non-lobar areas. ClinicalTrials.gov Identifier: NCT04803292, March 17, 2021 weblink: https://clinicaltrials.gov/ct2/show/NCT04803292